Anti quorum sensing and anti biofilm efficacy of cinnamaldehyde encapsulated chitosan nanoparticles against Pseudomonas aeruginosa PAO1. (November 2018) - Subhaswaraj, Pattnaik; Barik, Subhashree; Macha, Chandrasekhar; Chiranjeevi, Potu Venkata; Siddhardha, Busi
Abstract: The encapsulation of cinnamaldehyde into biodegradable polymeric systems represents a possible strategy to overcome the bioavailability issues and enhance the sustained release of the drug at the target sites. In the present study, the efficacy of cinnamaldehyde encapsulated chitosan nanoparticles (CANPs) in attenuating the quorum sensing (QS) regulated virulence of P. aeruginosa PAO1 was investigated. CANPs were synthesized by ionic gelation method, characterized by dynamic light scattering (DLS), and transmission electron microscopic (TEM) analysis. The DLS and TEM analysis confirmed the synthesis of CANPs with a mean diameter of 208.12 nm. The encapsulation efficiency was observed to be 65.04 ± 3.14% and in vitro release study confirmed the slow and sustained release of cinnamaldehyde. CANPs showed significant anti quorum sensing activity by down regulating the QS regulated virulence factors and associated biofilm formation as evidenced from microscopic observation. CANPs also significantly altered the swimming and swarming motility of P. aeruginosa PAO1. The present results suggested the greater prospective of the application of CANPs as potential anti quorum sensing agents as compared to native cinnamaldehyde and suggested new avenues for development of novel anti-infective agents in the post antibiotic era. Graphical abstract: Image 1 Highlights: Ionic gelation method was used for synthesis of CANPs. TEM analysis confirmed the synthesis of CANPs. Anti quorum sensing potential of CANPs against P. aeruginosa PAO1 was evaluated. Anti biofilm efficacy of CANPs was determined against P. aeruginosa PAO1. CLSM analysis corroborated the biofilm inhibition potential of CANPs.